Functional KRAS mutations and a potential role for PI3K/AKT activation in Wilms tumors. Issue 4 (15th March 2017) - Polosukhina, Dina; Love, Harold D.; Correa, Hernan; Su, Zengliu; Dahlman, Kimberly B.; Pao, William; Moses, Harold L.; Arteaga, Carlos L.; Lovvorn, Harold N.; Zent, Roy; Clark, Peter E.
Abstract : Wilms tumor (WT) is the most common renal neoplasm of childhood and affects 1 in 10 000 children aged less than 15 years. These embryonal tumors are thought to arise from primitive nephrogenic rests that derive from the metanephric mesenchyme during kidney development and are characterized partly by increased Wnt/β‐catenin signaling. We previously showed that coordinate activation of Ras and β‐catenin accelerates the growth and metastatic progression of a murine WT model. Here, we show that activating KRAS mutations can be found in human WT. In addition, high levels of phosphorylated AKT are present in the majority of WT. We further show in a mouse model and in renal epithelial cells that Ras cooperates with β‐catenin to drive metastatic disease progression and promotes in vitro tumor cell growth, migration, and colony formation in soft agar. Cellular transformation and metastatic disease progression of WT cells are in part dependent on PI3K/AKT activation and are inhibited via pharmacological inhibition of this pathway. Our studies suggest both KRAS mutations and AKT activation are present in WT and may represent novel therapeutic targets for this disease. Abstract : We show that human Wilms tumor (WT) can harbor KRAS‐activating mutations and that the majority of human WT exhibit high levels of AKT activation. Utilizing a novel murine WT cell line, we show that Ras and β‐catenin cooperate to accelerate tumor cell growth, migration, and colony formation in vitro and growth and metastatic disease progression of orthotopic grafts. Cellular transformation and metastatic progression are in part PI3K/AKT dependent and are inhibited through pharmacological inhibition of PI3K/AKT. Thus, targeting PI3K/AKT activation in WT may be a viable new treatment strategy.